1989
DOI: 10.1111/j.1558-5646.1989.tb05177.x
|View full text |Cite
|
Sign up to set email alerts
|

POPULATION DIFFERENTIATION AND RACIAL ADMIXTURE IN THE AFRICANIZED HONEYBEE (APIS MELLIFERA L.)

Abstract: To study the degree of interpopulational differentiation and racial admixture in Africanized honeybees, we collected worker bees from three regions of Brazil (the northeast, the state of Sao Paulo, and Porto Alegre) and from Uruguay and determined their genotypes for 10 enzyme loci. We also performed a morphometric analysis on forewing measurements of worker bees from the northeast and Porto Alegre regions of Brazil and from Paysandu, Uruguay. Comparative analysis of interpopulational heterogeneity snowed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 24 publications
2
55
1
2
Order By: Relevance
“…The diversity of allele frequencies at the MDH locus between the three Costa Rican regions is higher than the genetic variation that has been detected between Brazilian populations separated by distances of thousands of kilometers (Lobo et a!., 1989). However, Lama et al, 1990).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The diversity of allele frequencies at the MDH locus between the three Costa Rican regions is higher than the genetic variation that has been detected between Brazilian populations separated by distances of thousands of kilometers (Lobo et a!., 1989). However, Lama et al, 1990).…”
Section: Discussionmentioning
confidence: 72%
“…Comparative studies of behaviour, population dynamics and morphometrics have revealed that these new bee populations are very similar to their African ancestors (summarized by Michener, 1975;Winston, 1992). Genetic polymorphism data have supported this conclusion, except in some regions where higher frequencies of European alleles can be detected (Lobo et al, 1989;Rinderer et al, 1991;Sheppard et al, 1991b). The latter phenomenon may be a result of prior high population densities or continued introduction of other honeybee races and/or ecological constraints for Africanized bees.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Análise aloenzimática -Para estimar as heterozigosidades intra-loco ( Hi ) e média ( H ), extratos de tórax de operárias adultas foram analisados através de eletroforese horizontal em gel de amido (DEL LAMA et al 1985, 1988, 1990LOBO et al 1989) para os seguintes sistemas aloenzimáticos: malato desidrogenase (Mdh) nas amostras Européias e Africanizadas; esterases (Est-1 e Est-3), fosfoglucomutase (Pgm) e hexoquinase (Hk) nas amostras Africanizadas.…”
Section: Methodsunclassified
“…An example is the analysis of the genetic composition of the Africanized honeybee, the population of bees resulting from the introduction of Apis mellifera scutellata to Brazil in 1956 (Kerr, 1967;Michener, 1975). Estimation of the frequencies of some racial markers in these populations may reveal the existence or otherwise of interracial hybridization during the initial settlement of A. m. scutellata in Brazil, and its subsequent migration across the American continent Hall & Muraihidharan, 1989;Lobo et a!., 1989;Smith et a!., 1989;Del Lama eta!., 1990, Hall, 1990Smith, 1991).…”
Section: Introductionmentioning
confidence: 99%